Identification and expression profile analysis of circRNAs associated with goat uterus with different fecundity during estrous cycle - Xiaolong Du; Yufang Liu; Xiaoyun He; Lin Tao; Meiying Fang; Mingxing Chu (BMC Genomics)
Abstract Background The Yunshang Black Goat, a distinguished meat goat breed native to China, is renowned for its superior reproductive capabilities. Despite this, there is considerable phenotypic variability within the breed. During the reproductive cycle, the uterus plays a pivotal role, with its functions evolving in line with the different stages of the cycle. This study focuses on the uterine tissues, including both the endometrium and myometrium, of Yunshang Black Goats with high fecundity (HF) and low fecundity (LF) during the proliferative (FP) and secretory (LP) phases of the estrous cycle. By examining these tissues, we aim to elucidate the underlying molecular and physiological mechanisms of the observed differences in reproductive success. Results High-throughput sequencing was conducted, followed by bioinformatics analysis to identify the expression profiles of circRNAs. A total of 7,445 circRNAs were identified through the integration of findings from find_circ and CIRI2 software. Comparative analyses between the FPLF vs. FPHF and LPLF vs. LPHF revealed 149 differentially expressed (DE) circRNAs (94 up-regulated and 55 down-regulated) and 276 DE circRNAs (56 up-regulated and 220 down-regulated), respectively. The enrichment analysis indicated that the primary pathways involved were the Sphingolipid signaling pathway, MAPK signaling pathway, and GnRH signaling pathway, all of which are closely associated with cellular growth and development. Additionally, several key candidate genes were identified, such as FGF2 and MBTPS1. We also predicted a total of 281 miRNA-circRNA binding pairs, encompassing 263 circRNAs and 60 miRNAs, and simultaneously, 14 coding circRNAs were anticipated. Conclusion Based on the analysis, we have established the expression profiles of circRNAs during the follicular and luteal phases, respectively. Furthermore, using various analytical methods and data from high- and low-yield experimental control groups over different periods, we have identified multiple circRNAs that affect the high reproductive capacity of goats. Through enrichment analysis of the host genes of these circRNAs, we have discovered several key candidate genes. These findings provide fundamental data for the study of the molecular mechanisms underlying the fecundity of goats and pave the way for future genetic improvement strategies.